2018
DOI: 10.15226/sojmid/6/1/00190
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus Associated with Mobile Phones

Abstract: Mobile phones widely used in our day-to-day lives are potential reservoir for a number of bacteria including Staphylococcus aureus. The study was carried out from February to May 2017 with a major objective of screening methicillin-resistant S. aureus (MRSA) from mobile phones used by the staffs and students of Birendra Multiple Campus, Bharatpur, Nepal. Out of 212 swabbed samples of mobile phones analysed by standard microbiological technique, 112 (56.0%) showed the presence of S. aureus. Gentamicin 101 (90.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Disinfected helmets showed the lower rate of microbial growth than that of nondisinfected helmets ( p < 0.05). This result was in line with a study done in Nepal which showed the lower rate of microbial growth in disinfected mobiles phones [ 8 ]. Disinfection processes can actively kill the microbes from inanimate surfaces that lead to the reduction of microbial count [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Disinfected helmets showed the lower rate of microbial growth than that of nondisinfected helmets ( p < 0.05). This result was in line with a study done in Nepal which showed the lower rate of microbial growth in disinfected mobiles phones [ 8 ]. Disinfection processes can actively kill the microbes from inanimate surfaces that lead to the reduction of microbial count [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The emergence of MRSA, ESBL, and MBL producing bacteria has become a serious concern. This study reported 33.7% of the Staphylococcus aureus as MRSA which was in tune with the previous study done in nonclinical samples [ 8 , 33 , 37 ]. ESBLs are plasmid mediated TEM and SHV-type enzymes capable of hydrolysing penicillins, broad-spectrum cephalosporins, and monobactams [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…None of the S. aureus isolates were resistant to vancomycin which is consistent with previous works, as most of the studies have shown that drugs like vancomycin and gentamicin have high efficacy but azithromycin, ampicillin, and co-trimoxazole have lower efficacy. [31][32][33] A total of 55.9% of the S. aureus isolates resisted cefoxitin and were Oxacillin-resistant and hence termed as MRSA. Distribution of MRSA in the present study was slightly higher than other studies, as studies by Rolston et al and Bhat et al both recorded a MRSA isolation rate of 40.0%.…”
Section: Discussionmentioning
confidence: 99%